A Turn-off Fluorescent Chemosensor for Detecting Formaldehyde Based on Pyridine Derivative - Nurul Hidayah; Bambang Purwono (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Formaldehyde in solution, commonly known as formalin, is often utilized. In Indonesia, there is widespread misuse of formalin as a food preservative. Formaldehyde has been identified as a carcinogenic substance by the International Agency for Research on Cancer (IARC) and the Environmental Protection Agency (EPA). Based on this background, the present study developed a sensor compound capable of detecting formaldehyde obviously. The compound 3'-(4-(3,4-dimethoxyphenyl)pyridine-2,6-diyl)dianiline (ChP-2A) has been successfully synthesized through the reduction reaction of the compound 4-(3,4-dimethoxyphenyl)-2,6-bis(3-nitrophenyl)pyridine (ChP-0A) using 80% hydrazine hydrate and 10% Pd/C as a catalyst. The ChP-2A compound in acetonitrile exhibits a significant decrease in fluorescence intensity (turn-off) after the addition of formaldehyde, and it has been successfully applied in the form of a test paper for the detection of formaldehyde qualitatively